Sharing RF spectrum with commodity wireless technologies theory and practice - Kruys, Jan; Qian, Luke.; SpringerLink (Online service). (Dordrecht Springer, 2011)
This book is about the theory and practice of spectrum sharing and is aimed at a wide audience. Although it addresses basic technical issues, the emphasis is on practice rather than theory. In presenting an overall picture of spectrum sharing, this book covers the why--the regulatory aspects as well as the how--the technical aspects. The latter is supported with a theoretical taxonomy of dimensions, modes and means of spectrum sharing and a number of practical cases of spectrum sharing are discussed, using established technologies as examples. This book should prove accessible to wireless systems designers, RF engineers and protocol developers as well as to planners for large scale wireless LAN deployments. The combination of theoretical explanation and practice based analysis is expected to prove useful for radio spectrum managers and regulators as well as standards development organizations. Further, this book should prove useful for educators and students in that it provides practice oriented background for the more abstract material presented in textbooks dealing with radio spectrum related theory.
Part I: RF Spectrum Sharing: Background and Theory -- 1. RF Spectrum, Usage and Sharing -- 2. Radio Regulations and Policies -- 3. Dimensions of Spectrum Sharing -- 4. Modes and Means of Spectrum Sharing -- 5. The Physics of Spectrum Sharing -- 6 .Medium Access Etiquettes and Protocols -- Part II: The Practice of Spectrum Sharing -- 7. Spectrum Sharing with Wireless LANS -- 8.Spectrum Sharing with Other Commodity Technologies -- 9. Sharing with Primary Spectrum Users -- 10. Radio Resource Management -- Part III: Prospects -- 11. Emerging Applications of Wireless Technologies -- 12. The Future of RF Spectrum Sharing -- Appendix A: Ofcom's Technical Studies -- Appendix B: DFS -Background and Compliance -- Appendix C: Radio Resource Management and Wireless Network Management Systems.
Electronic reproduction.
Keywords: Spectrum analysis; Wireless communication systems; Electronic books